Waters of the Exodus: Jewish experiences with water in Ptolemaic and Roman Egypt - LaCoste, Nathalie (Journal for the study of Judaism / Supplements, 2019)
Jewish life within Egypt: a regional analysis of Judaism in Ptolemaic and Roman Egypt -- Exodus narratives of Egypt: shared characteristics -- Adopting the language of the environment of Egypt: hydric terminology in the Exodus narratives -- Challenges and observations: hydric terminology and the Jews of Egypt -- The quest for origins: Jewish perspectives on the source of the Nile flood -- The Etesian winds of Egypt and the impious Egyptians : Philo's life of Moses -- Conclusion: the fluvial experiences of the Jews of Egypt